Pengaruh Menonton Film Negeri 5 Menara Terhadap Motivasi Belajar Santri Pondok Pesantren Tarbiyatus Shibyan Bagan Batu - Bayu Wardana; Daryanto Setiawan; Taufik Hidayat (PT. Hasba Edukasi Mandiri, 2025)
The film Negeri 5 Menara is a popular and frequently watched movie among students at Tarbiyatus Shibyan Islamic Boarding School in Bagan Batu. This research aims to determine the influence of watching Negeri 5 Menara on the learning motivation of students at Tarbiyatus Shibyan Islamic Boarding School, Bagan Batu. This study employs a quantitative associative approach with a causal relationship. The population consists of 414 individuals, while the sample size is 80 individuals, selected using Random Sampling. Data analysis utilizes the Product Moment correlation, aided by the SPSS application. The analysis reveals a positive and significant influence of variable X (watching the film Negeri 5 Menara) on variable Y (learning motivation). This is evident in the coefficient value at a 5% significance level, with r = 0.413, indicating a moderately strong correlation. The contribution of watching Negeri 5 Menara to learning motivation is 17.05%, while the remaining 82.95% is influenced by other variables not included in this study.